Variability in the size of airspaces in normal human lungs as estimated by aerosols. - Lapp, N L (1975)
Measurement of persistence, expressed as half-life (t1/2), of a monodisperse aerosol during breath holding was interpreted as an indirect estimate of the size of intrapulmonary airspaces in healthy subjects. Within subject variation of t1/2 measured over a period of nearly two years was small (coefficient of variation 7-7 to 11-5%). Mean effective airspace diameters were calculated from the aerosol t1/2 values using the settling term from the equation of Landahl (1950). Calculated mean airspace diameters ranged from 0-30 to 0-79 mm for 36 males and from 0-40 to 0-62 mm for 12 females. Airspace diameters correlated poorly with age, height, weight, and lung volumes. These results suggest marked differences in airways geometry in subjects with similar heights and lung volumes.